PENGARUH MEDIA WORDWALL TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN FIQIH DI MTSN 1 KOTA PAYAKUMBUH - Nurul Fatiha; Nurhasnah Nurhasnah; Fajriyani Arsya; Darul Ilmi (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
Researchers conducted research at MTsN 1 Payakumbuh City which was caused by health factors that influenced students' interest in fiqh and students' low understanding of the subject. Apart from that, many students deviate from the lesson and do not listen according to the teacher's explanation. This quantitative research involved 60 students. Normality Test, Kolmogrov Smirnov statistical test, Homogeneity Test, Hypothesis Test, followed by the Coefficient determination test. From the results of research and data analysis, it was found that learning was less capable. With a significance level of 5%, the t test calculation showed that tcount = 0.000 < 0.005. This shows that the hypothesis shows that the wordwall learning media influences students' interest in studying fiqh at MTsN 1 Payakumbuh City. increase students' enthusiasm and interest in education, moreover the source of knowledge in the learning process is still controlled by the teacher so that it makes students active. rarely plays a role. The aim of this research is to see the effect of wordwall as a learning medium on students' interest in learning fiqh at MTsN 1 Payakumbuh City. There are health factors that influence students' interest in learning.